Advance Without Cut and Retrograde Removal of Embedded Fishhook; Introducing a Novel Technique - Pakniyat, Abdolghader; Akhbari , Kourosh; Radfar, Fatemeh (Archives of Academic Emergency Medicine, 2022)
Removing embedded fishhook without causing further tissue damage from the barbed nature of the hook is a challenge in emergency department (ED). The four most commonly used techniques include advance and cut, string-yank, needle cover, and retrograde removal. This study aims to describe a modified push- through technique without cutting the barb, namely advance without cut and retrograde removal, as an effective technique of successful removal of fishhooks. There is no risk of additional injury to patients and healthcare staff, and the technique does not need tools that are not generally readily available in EDs.